2011
DOI: 10.1007/s10495-011-0611-3
|View full text |Cite
|
Sign up to set email alerts
|

Shogaols at proapoptotic concentrations induce G2/M arrest and aberrant mitotic cell death associated with tubulin aggregation

Abstract: Shogaols have been previously reported to induce cancer cell death via multiple mechanisms, among which one analog 6-shogaol has been reported to cause microtubule damage through specific reaction with sulfhydryl groups in tubulin. In this study, a series of shogaols with different side chain lengths (4-, 6-, 8- and 10-shogaol) was synthesized and evaluated for antiproliferative activity in HCT 116 colon carcinoma and SH-SY5Y neuroblastoma cells. 4- and 6-shogaol were identified as lead compounds possessing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…Soft agar colony-formation assays were carried out after treatment with wogonoside for 4 days. 19 The colonies were viewed at 340 magnification to detect colony size and colony numbers, using an inverted microscope equipped with a color camera (Nikon Instruments Inc, Lewisville, TX). In vivo investigations were performed in BALB/c nude mice injected with U937 cells 20 and in nonobese diabetic/severe combined immunodeficiency (NOD/SCID) immunodeficient mice engrafted with primary human AML cells.…”
Section: Cell Culturementioning
confidence: 99%
“…Soft agar colony-formation assays were carried out after treatment with wogonoside for 4 days. 19 The colonies were viewed at 340 magnification to detect colony size and colony numbers, using an inverted microscope equipped with a color camera (Nikon Instruments Inc, Lewisville, TX). In vivo investigations were performed in BALB/c nude mice injected with U937 cells 20 and in nonobese diabetic/severe combined immunodeficiency (NOD/SCID) immunodeficient mice engrafted with primary human AML cells.…”
Section: Cell Culturementioning
confidence: 99%
“…The compound was also reported to inhibit breast cancer cell invasion by reducing MMP-9 expression via targeting the NF- k B activation cascade [9] or by inhibiting invade podium formation [12]. Our group and Gan et al have found that 6-shogaol induced G2/M cell cycle arrest and apoptosis characterized by caspase 3 and PARP cleavage in HeLa and HCT116 cells [3,13]. Despite enormous efforts performed to investigate the anticancer activities of 6-shogaol, to date, the study on induction of apoptosis induced by 6-shogaol in human leukemia cells has not yet been explored, nor have the relationships between 6-shogaol-mediated anti-leukemic activity and cell signaling cascades been examined in depth.…”
Section: Introductionmentioning
confidence: 99%
“…6-Shogaol was described to not only have anti-cancer and anti-inflammatory capabilities, but also had the potential to be used as an anti-metastatic treatment [18]. At pro-apoptotic concentrations, 10-shogaol, an extract from ginger, was able to induce G(2)/M arrest and abnormal mitotic cell death that is associated with tubulin aggregation [19]. 10-Shogaol, the only non-pungent compound among the gingerols and shogaols, has the ability to stimulate the increase of adrenaline secretion [20].…”
Section: Introductionmentioning
confidence: 99%